(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Nurses are responsible for the bedside care of the patient. They may witness many patient’s death at work. A high level of nurses’ death anxiety can impede the quality of patient care, especially in the final stages of patient life. This study was conducted to describe the level of death anxiety among nursing students. Objectives: This study aimed to describe the level of death anxiety among nursing students at Thai Nguyen University of Medicine and Pharmacy in 2022. Methods: A cross-sectional descriptive study was conducted on a convenient sample of 130 full-time nursing students studying at the Thai Nguyen University of Medicine and Pharmacy in April 2022. The Vietnamese version of the Templer Death Anxiety Scale (TDAS) was used to assess the level of death anxiety. The total anxiety score is 15 and was classified into three categories, which were No anxiety (0-5), Moderate (6-10), and High (11-15). Results: Most nurses in this study were female (95.4%) with an average age of 20.35 ± 1.16. They have no experience caring for family members but have opportunities to care for dying patients during their studies/work, with a prevalence of 87.7% and 94.6%, respectively. Nursing students’ overall death anxiety level was moderate, with an average score of 6.81 ± 2.43. Fifty percent had no anxiety, 33.1% had moderate anxiety, and 16.9% were very anxious about death. Conclusion: Interventions are needed to help nursing students overcome and manage their death anxiety, which can improve the quality of care for dying persons.